Nucleic‐Acid Structures as Intracellular Probes for Live Cells. Issue 13 (4th July 2019) - Samanta, Devleena; Ebrahimi, Sasha B.; Mirkin, Chad A.
Abstract: The chemical composition of cells at the molecular level determines their growth, differentiation, structure, and function. Probing this composition is powerful because it provides invaluable insight into chemical processes inside cells and in certain cases allows disease diagnosis based on molecular profiles. However, many techniques analyze fixed cells or lysates of bulk populations, in which information about dynamics and cellular heterogeneity is lost. Recently, nucleic‐acid‐based probes have emerged as a promising platform for the detection of a wide variety of intracellular analytes in live cells with single‐cell resolution. Recent advances in this field are described and common strategies for probe design, types of targets that can be identified, current limitations, and future directions are discussed. Abstract : Nucleic acid‐based sensors such as hybridization‐based probes, aptamers, and DNAzymes have emerged as key tools for studying analytes in live cells. The current state of intracellular nucleic‐acid‐based probes is described and common strategies for probe design, what targets can be detected, and how current limitations may be overcome in the future are discussed.